Legged Saddle Querns of South Asia - Weisshaar, Hans-Joachim (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Legged saddle querns to grind spices and herbal medicine were used from ancient times up to the present day. At times they were placed as offerings which is unusual for objects of daily life. One example is the foundation deposit of the hospital phase on the Citadel of Tissamaharama, 1st century A. D. A second example is an offering pit underneath the pavement of the Yatala Dagoba of uncertain date. Sometimes the surfaces of the querns are decorated with simple ornaments and from time to time they carry auspicious symbols.The article will be available as a PDF in the near future.